Qualitative traits of aged m. Triceps brachii and m. gluteus biceps from lambs on supplemented feed - Ferrari, Fabio Borba [UNESP]; de Mello, Juliana Lolli Malagoli [UNESP]; de Oliveira, Rodrigo Fortunato [UNESP]; de Souza, Rodrigo Alves [UNESP]; Ferrari, Viviane Borba; Giampietro-Ganeco, Aline [UNESP]; de Lima, Flavia Biondi Fernandes [UNESP]; de Souza, Pedro Alves [UNESP]; Borba, Hirasilva [UNESP] (Faculty of Veterinary Medicine, University of Zagreb, 2018)
The aim of this study was to evaluate the effect of the supplementation and aging in the gluteus biceps and triceps brachii muscles of lamb. Forty-eight Santa Inês lambs, with 15 kg average initial weight were slaughtered at 32 kg average final weight, after five months of supplementation. Twenty-four animals were allocated to sixteen pastures with residual leaf area index (2.6) and unsupplemented, the other twenty-four animals were allocated to the same conditions but were supplemented. The treatments were cross factorial between rLAI (2.6) and supplemented or not, totalizing 8 treatments. In this experiment, the slaughter criterion was the age of the animals. In the gluteus biceps and triceps brachii muscles, storage for seven days increased lipid oxidation. The values of cooking loss and water holding capacity increased with time of aging and were higher in the gluteus biceps, by 29.40% and 71.30%, respectively. The supplementation implies an increase in production costs, but its use provides the quantitative and qualitative characteristics favorable to the product, aiming to satisfy the consumer market. The supplementation decreased the shelf life, increasing the lipid oxidation during time of aging and affected the lightness and the hue of yellow, which may sffect consumers’ intention to purchase.
Keywords: Lipid oxidation; Myofibrillar fragmentation index; Redness; Shear force; Shelf life; Tenderness; Yellowness